Reindeer Herding and Youth: Project proposal. Arctic Council Sustainable Development Working Group. - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group (SDWG), 2011)
Justification of the new action including relations to a priority subject area, activity of other working groups and contribution to gender equality. This project is related to several key and priority areas of importance highlighted by the Arctic Council in the Nuuk Declaration of 2011 and the recommendations from the 9th Conference of Parliamentarians of the Arctic region in 2010. This project represents a continuation of the legacy of both ACIA and IPY, and is an IPY legacy project. Furthermore it is linked to the strategic goals of the Russia’s Arctic Policy to 2020 and Beyond adopted in 2008 and the Russian Federation Climate Change Doctrine 2009. With reference to the daunting challenges reindeer herding in the north face as a result of projected climate change, land use change and societal changes in the north the coming decades, IPY EALAT has concluded that adaptation to change demands the training of local Arctic leaders in long term sustainable thinking. This project focuses on training and engagement of indigenous reindeer herding youth who represent the sustainable future of reindeer herding and other traditional livelihoods in the Arctic. The meaningful engagement of indigenous peoples for the future is.”.fundamental to addressing circumpolar challenges and opportunities” (Tromso Declaration, 2009), and the continued engagement of indigenous peoples and communities is emphasized “.as a fundamental strength of the Council” (Nuuk Declaration, 2011). This must clearly also apply to engagement of indigenous youth. ￼Climate change and socio-economic change are now evident across the Arctic, and is particularly evident in reindeer herding cultures and in their traditional areas. Global and regional scenarios project dramatic changes in temperature, precipitation and snow conditions in the key areas for reindeer herding and in social-economic changes for reindeer herding communities and other indigenous communities in the Arctic. Degradation of pasture lands combined with the consequences of a changing ...